Prominent positioning and food swaps are effective interventions to reduce the saturated fat content of the shopping basket in an experimental online supermarket: a randomized controlled trial - Koutoukidis, D; Jebb, S; Ordóñez-Mena, J; Noreik, M; Tsiountsioura, M; Kennedy, S; Payne-Riches, S; Aveyard, P; Piernas, C (BioMed Central, 2019)
Background Interventions to reduce the saturated fat (SFA) content of food purchases may help reduce SFA consumption and lower cardiovascular risk. This factorial RCT aimed to examine the effect of altering the default order of foods and being offered a swap on the SFA content of food selected during an online shopping experiment. Methods UK adults who were the primary grocery shoppers for their household were recruited online and invited to select items in a custom-made experimental online supermarket using a 10-item shopping list. Participants were randomly allocated to one of four groups (i) to see products within a category ranked in ascending order of SFA content, (ii) receive an offer to swap to a product with less SFA, (iii) a combination of both interventions, or (iv) no intervention. The primary outcome was the difference in percentage energy from SFA in the shopping basket between any of the four groups. The outcome assessors and statistician were blinded to intervention allocation. Results Between March and July 2018, 1240 participants were evenly randomised and 1088 who completed the task were analysed (88%). Participants were 65% female and aged 38y (SD 12). Compared with no intervention (n = 275) where the percentage energy from SFA was 25.7% (SD 5.6%), altering the order of foods (n = 261) reduced SFA by [mean difference (95%CI)] -5.0% (− 6.3 to − 3.6) and offering swaps (n = 279) by − 2.0% (− 3.3 to − 0.6). The combined intervention (n = 273) was significantly more effective than swaps alone (− 3.4% (− 4.7 to − 2.1)) but not different than altering the order alone (− 0.4% (− 1.8 to 0.9)), p = 0.04 for interaction. Conclusions Altering the default order to show foods in ascending order of SFA and offering a swap with lower SFA reduced percentage energy from SFA in an experimental online supermarket. Environmental-level interventions, such as altering the default order, may be a more promising way to improve food purchasing than individual-level ones, such as offering swaps. Trial registration ISRCTN13729526 https://doi.org/10.1186/ISRCTN13729526 26th February 2018.